Te Ao Kori in New Zealand Physical Education: A Narrative Literature Review - Kaukau, A; Smith, S; Karaka-Clarke, TH (Informa UK Limited, 2025)
Te Ao Kori represents an Indigenous Māori worldview of Physical Education. Its introduction into New Zealand's Physical Education curriculum was an effort to integrate Māori perspectives on movement into mainstream education. Over time, interpretations of Te Ao Kori have varied, ranging from a surface-level focus on playing traditional Māori games to more holistic teaching and learning embedded in Māori worldviews. While culturally responsive frameworks and Treaty knowledge have developed, there has been no comprehensive review of how Te Ao Kori has been conceptualised and evolved in Physical Education literature. This paper seeks to remedy this. A narrative review methodological approach was chosen to align with Māori storytelling traditions, enabling a holistic and reflexive analysis of the literature. This allowed for critical engagement with diverse sources, capturing the evolution of discourse surrounding Te Ao Kori. The result is a socio-cultural narrative review of Te Ao Kori that identifies historical, pedagogical, and socio-political influences shaping its understanding and use. Findings indicate that while Te Ao Kori is acknowledged in curriculum documents, there is little research on how this translates to practice. This narrative literature review highlights the conceptual evolution of Te Ao Kori but simultaneously exposes the need for clearer frameworks to support meaningful understanding and use in Physical Education. Without support, Te Ao Kori’s inclusion risks being ‘referenced’ rather than being meaningfully embedded. The paper provides insights for educators and policymakers to move beyond symbolic inclusion toward the development of curriculum and teaching approaches that authentically embed Māori epistemologies. Moreover, it adds to the increasing body of global literature on indigenous knowledge in bicultural and multicultural educational environments.
Keywords: 1301 Education Systems; 1302 Curriculum and Pedagogy; 1303 Specialist Studies in Education; Sport Sciences; 3901 Curriculum and pedagogy; 3904 Specialist studies in education; 4207 Sports science and exercise